1987
DOI: 10.1007/bf01254085
|View full text |Cite
|
Sign up to set email alerts
|

Hyperlactat�mie bei Darmisch�mie

Abstract: Looking for an early laboratory parameter in diagnosis of acute bowel ischemia, we caused an acute ischemia of the rabbit bowel by clamping the superior mesenteric artery. The blood tests showed a significant increase of lactate during 80 min of ischemia. This lactate excess continued nearly 40 min after revascularization of the bowel, but disappeared nearly completely after 90 min. Neither the laparotomy without clamping the superior mesenteric artery, nor the experimental clamping of the a. femoralis communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Nutz et al [27] performed a study in which they cross-clamped the superior mesenteric artery in rabbits, and they noted increased serum lactate until about 40 min after revascularization of the bowel, which was absent after cross-clamping of the common femoral artery. Similar observations were made after occlusion of the superior mesenteric artery as opposed to, for example, clamping of celiac vessels [28,29].…”
Section: Experimental Studies On Serum Lactate Levels In Acute Mesentmentioning
confidence: 99%
“…Nutz et al [27] performed a study in which they cross-clamped the superior mesenteric artery in rabbits, and they noted increased serum lactate until about 40 min after revascularization of the bowel, which was absent after cross-clamping of the common femoral artery. Similar observations were made after occlusion of the superior mesenteric artery as opposed to, for example, clamping of celiac vessels [28,29].…”
Section: Experimental Studies On Serum Lactate Levels In Acute Mesentmentioning
confidence: 99%
“…(16) These kinds of studies continue during the 21 st century where some studies confirmed the relation and others didn't confirm the relation. (17,18) Several experimental studies were conduct with debatable findings and without providing conclusive evidences of the efficacy of using serum lactate level as marker for AMI, in study on rabbits by Nutz et al , the authors observed increasing in the level of serum lactate among the subjects with occlusion of the superior mesenteric artery , these results couldn't be confirmed in 1995 study on pigs conducted by Schlichting and Lyberg, (19,20) In addition to that several experimental studies during the first decade of 21 st century concluded that serum lactate level is not a specific and early diagnostic marker for AMI. (13,21,22) Several prospective clinical studies on lactate levels andacute mesenteric ischemia were conduct , from these studies the two studies conduct 1994 and 1997 by Lange and Jackel and also Lange and Toivola where the authors concluded that even with the high sensitivity of serum lactate the specificity was low which mean that doctors couldn't rely on serum lactate as specific markers.…”
Section: And6and Figures 56 And7)mentioning
confidence: 98%